Religious Character Values in the Novel Promise by Tere Liye and Its Relevance to Islamic Religious Education and Ethics Materials in Senior High School - Kusna, Ilma Fadhilatul; Kusumaningrum, Endah (Islamic Studies Journal, 2023)
The issue of character degradation of the younger generation is increasing. Efforts are needed to shape the character of this generation, one of which is by instilling religious character. The implementation can be through Islamic religious education and ethics as well as reading literary works such as the novel Janji by Tere Liye. This study aims to describe the religious characters in the novel Janji by Tere Liye and analyse the relevance of religious characters contained in the novel Janji by Tere Liye with Islamic religious education and ethics materials in high school. This research was conducted using library research method and descriptive qualitative type. The results found in this study, the novel Janji by Tere Liye contains religious character values, namely 1) The value of worship which includes establishing prayer, the intention to go on pilgrimage, and prayer. 2) The value of ruhul jihad which includes teachers educating their students and employees towards their work. 3) Moral and disciplinary values which include gratitude, repentance, honesty, not gossiping, tolerance, helping, and generosity. 4) Exemplary values which include employees towards their bosses, citizens towards the community, and among friends. 5) The value of trust which includes fulfilling duties and delivering messages, and the value of sincerity which includes letting go and accepting fate. The five values contained in the novel Janji have relevance to Islamic Religious Education and Cultivation materials in high school.